The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.3389/fmicb.2020.625450
|View full text |Cite
|
Sign up to set email alerts
|

A Bacterium Isolated From Soil in a Karst Rocky Desertification Region Has Efficient Phosphate-Solubilizing and Plant Growth-Promoting Ability

Abstract: Phosphorus in the soil accessible to plants can easily be combined with calcium ion, the content of which is high in karst rocky desertification (KRD) regions, thereby resulting in a low utilization efficiency of phosphorus. The application of phosphate-solubilizing bacteria (PSB) from the KRD region would facilitate enhanced phosphate availability in the soil. In the present study, the strains belonging to Acinetobacter, Paraburkholderia, and Pseudomonas with efficient phosphate-solubilizing ability were isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 44 publications
0
12
1
Order By: Relevance
“…The inoculation of PSB can alter community function of soybean rhizosphere bacteria and increase P-cycling-related gene abundance and thus enhance vegetation properties ( 24 ). Previous reports have also reported that inorganic phosphate-solubilizing bacteria can release oxalic, lactic, malic, citric, succinic, and indole-3-acetic acid to enrich soluble P levels ( 9 , 23 , 53 , 57 ). The gcd -harboring bacteria can release gluconic acid via oxidizing gluconate by producing gluconate dehydrogenase ( 40 , 57 ).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The inoculation of PSB can alter community function of soybean rhizosphere bacteria and increase P-cycling-related gene abundance and thus enhance vegetation properties ( 24 ). Previous reports have also reported that inorganic phosphate-solubilizing bacteria can release oxalic, lactic, malic, citric, succinic, and indole-3-acetic acid to enrich soluble P levels ( 9 , 23 , 53 , 57 ). The gcd -harboring bacteria can release gluconic acid via oxidizing gluconate by producing gluconate dehydrogenase ( 40 , 57 ).…”
Section: Discussionmentioning
confidence: 92%
“…Previous reports have also reported that inorganic phosphate-solubilizing bacteria can release oxalic, lactic, malic, citric, succinic, and indole-3-acetic acid to enrich soluble P levels ( 9 , 23 , 53 , 57 ). The gcd -harboring bacteria can release gluconic acid via oxidizing gluconate by producing gluconate dehydrogenase ( 40 , 57 ). Future studies will investigate the growth-promoting performances of Pseudomonas sp.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In addition, the inoculation of E. cloacae NG-33 strain into sandy soils dramatically increased the soluble phosphate could be mainly attributed to the more production of organic acids (i.e., tartaric acid, oxalic acid, acetic acid, and citric acid) into the rhizosphere to solubilize and release the available P from insoluble P pools. Microbes can solubilize inorganic phosphate compounds in the rhizosphere by releasing a variety of organic compounds into the environment ( Scervino et al, 2010 ; Xie et al, 2021 ). However, the inoculation of NG-33 strain also increased leaf P n and plant biomass in loamy soil without the supplemental TCP, likely due to the high production of IAA (20.4 μg ml −1 ) by NG-33.…”
Section: Discussionmentioning
confidence: 99%
“…Microbial P-solubilization was first reported in the early 20th century, with observations that some bacterial strains isolated from soil were capable of liberating phosphate from bone meal and phosphate ore [ 9 , 10 ]. Subsequently, numerous highly efficient soil-borne phosphorus-solubilizing bacteria (PSB) have been isolated from a range of agricultural and natural environments including diverse rhizosphere soils [ 11 ] and karst rocky deserts [ 12 ]. Phosphate-solubilizing micro-organisms can convert insoluble P into soluble forms (primarily phosphate) that can be readily absorbed and utilized by plants [ 6 ].…”
Section: Introductionmentioning
confidence: 99%